If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a = 2a + 4 Reorder the terms: 3a = 4 + 2a Solving 3a = 4 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 3a + -2a = 4 + 2a + -2a Combine like terms: 3a + -2a = 1a 1a = 4 + 2a + -2a Combine like terms: 2a + -2a = 0 1a = 4 + 0 1a = 4 Divide each side by '1'. a = 4 Simplifying a = 4
| ht=19+32t+16t^2 | | (5xy)2= | | 4x-2y=-1 | | 6+y=8 | | 10=3-m | | -7+8u=7u-2 | | h(t)=-16t^2+32t+19 | | 4+-5x=-36 | | ab-cd=0 | | -x+12=-9 | | r=s-t | | j+8=7 | | 2x=4y | | 4(x+1)=2(x-3)-(1-2x) | | b-13=24 | | 4+13x=36 | | 6x-4(x+1)=2(x-3)+2 | | 5x+17=15x-83 | | 5x+2(3x-1)=x | | 4(x-1)-3x=-2x-4+3x | | 9+6w=-2+6w | | 3x+34-8x=11-9x-13 | | 0.4x+3.91=21.05 | | 12x-29=6x+1 | | -4c-5c=-9c | | 4.5(x-2)+1.5=2(3x-4)-1 | | 34y-4=7+12y | | 7z=4z+3z | | 4x-7=x+1 | | -3(x+2)=-18 | | -10j=6-10j | | 3x-2(x+3)=4x-7 |